A N/S/O-tridoped hard carbon network anode from mercaptan/polyurethane-acrylate resin for potassium-ion batteries. (March 2021) - Chen, Mei; Cao, Yaping; Ma, Cong; Yang, Huai
Abstract: Hard carbon is a promising anode material for potassium-ion batteries (KIBs) due to its disordered and nonexpendable framework. However, the potassium storage performance in hard carbon still needs to be further improved. In this paper, functional nitrogen, sulfur and oxygen tri-doped hard carbon network (NSO-HCN), prepared through a carbonization-etching strategy using the precursor of mercaptan/polyurethane-acrylate (MPUA) resin, was promoted as the anode for KIBs. The obtained amorphous NSO-HCN possessed a porous 3D interconnected carbon network structure with an expanded interlayer distance (0.391 nm) and a large Brunauer–Emmett–Teller (BET) specific area (500.4 m 2 /g). These features allowed the NSO-HCN to deliver a high potassiation capacity of 209.6 mAh/g at 50 mA/g over 100 cycles and a favorable cycling stability by preserving potassiation capacities of 184.2, 146.8, and 136.0 mAh/g over 200 cycles at 100, 200 and 500 mA/g, respectively. Graphical Abstract: A nitrogen, sulfur and oxygen tri-doped hard carbon network (NSO-HCN), prepared through a carbonization-etching strategy using the precursor of mercaptan/polyurethane-acrylate (MPUA) resin, was designed and prepared as a novel anode for boosting KIBs in term of capacity and cycling stability. ga1 Highlights: Functional N/S/O tri-doped hard carbon network, was designed and prepared through a carbonization-etching strategy. A porous 3D interconnected carbon network with an expanded interlayer distance and a large BET area can be obtained. The obtained amorphous NSO-HCN anode delivered a high potassiation capacity and a favorable cycling stability.